PENGARUH METODE GAME BASED LEARNING TERHADAP HASIL BELAJAR PADA MATA PELAJARAN MATEMATIKA SISWA KELAS III SD SWASTA ASSISI TEBING TINGGI - Reynaldi Lumban Gaol; Janwar Tambunan; Theresia Siahaan (STKIP Subang, 2026)
This study aims to determine the effect of the Game Based Learning (GBL) method on the mathematics learning outcomes of third-grade students of Assisi Tebing Tinggi Private Elementary School. The background of this study is the low student learning outcomes in multiplication and addition materials, where only 25% of students achieved the KKM (70) due to the monotonous lecture method. The research method used is quantitative with a pre-experimental design of the One-Group Pretest-Posttest Design type. The research sample consisted of 30 third-grade students selected using the total sampling technique. Data collection was carried out through essay tests that had passed validity and reliability tests with a Cronbach's Alpha value of 0.908. The results of data analysis showed an increase in the average value from 71.66 in the pretest to 83.66 in the posttest. Based on the hypothesis test (t-test) using SPSS 21, the t-count value was 12.081 which was greater than the t-table of 1.699 12.081 > 1.699 with a significance level of 0.000 0.000 < 0.05. These results indicate that H0 is rejected and Ha is accepted. Thus, it can be concluded that there is a significant positive influence of the use of the Game Based Learning method on the mathematics learning outcomes of grade III students of Assisi Tebing Tinggi Private Elementary School in the 2025/2026 Academic Year.